Competition in tourism arrivals: a multidimensional index of geographical structural similarity - Crespo, N.; Simões, N. N.; Duarte, J. M. (Tourism Analysis, 2016)
Given the economic importance of the tourism sector, countries actively compete for attracting tourism flows. In a bilateral perspective, an important determinant of the degree of competition is the geographical structure of tourism inflows (i.e., the relative importance of the different source countries). A higher overlap of these flows indicates greater competition. The present study proposes a methodological approach to quantify this overlap. Taking some indicators traditionally used in international trade analysis as inspiration, we propose a methodology that measures, for each pair of countries, the degree of similarity between the geographical structures of tourism inflows. The methodology takes a multidimensional concept of structural similarity in order to incorporate relevant dimensions of international tourism flows today